SH3 interactome conserves general function over specific form - Xiaofeng Xin; David Gfeller; Jackie Cheng; Raffi Tonikian; Lin Sun; Ailan Guo; Lianet Lopez; Alevtina Pavlenco; Adenrele Akintobi; Yingnan Zhang; Jean‐François Rual; Bridget Currell; et al. (Molecular Systems Biology, 2013)
Abstract Src homology 3 (SH3) domains bind peptides to mediate protein–protein interactions that assemble and regulate dynamic biological processes. We surveyed the repertoire of SH3 binding specificity using peptide phage display in a metazoan, the worm Caenorhabditis elegans, and discovered that it structurally mirrors that of the budding yeast Saccharomyces cerevisiae. We then mapped the worm SH3 interactome using stringent yeast two‐hybrid and compared it with the equivalent map for yeast. We found that the worm SH3 interactome resembles the analogous yeast network because it is significantly enriched for proteins with roles in endocytosis. Nevertheless, orthologous SH3 domain‐mediated interactions are highly rewired. Our results suggest a model of network evolution where general function of the SH3 domain network is conserved over its specific form.